(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2014)
The stem bark of Garcinia lanceifolia, a lesser known species of the genus Garcinia, was extracted with methanol after pretreatment with petroleum ether. The resultant extract was evaluated for its analgesic and anti-inflammatory potential using various models. The assays were carried out on adult male Wistar Albino rats. The analgesic activity was assayed by hot plate method and tail flick assay using Morphine sulphate as standard drug at a dose of 5 mg/kg body weight and the results were expressed as mean increase in latency after drug administration ± SEM. The anti-inflammatory activity was evaluated by Carrageenan-induced rat paw oedema model using Diclofenac sodium as standard drug at a dose of 100 mg/kg body weight. The results were expressed in terms of mean increase in paw volume ± SEM. The extract of the stem bark was given in doses of 250 mg/kg and 500 mg/kg body weight. All the doses were administered per orally. Results reveal that Garcinia lanceifolia Roxb. posseses remarkable analgesic and anti-inflammatory activities.